2014
DOI: 10.1177/0960327114554047
|View full text |Cite
|
Sign up to set email alerts
|

Edaravone ameliorates the adverse effects of valproic acid toxicity in small intestine

Abstract: Valproic acid (VPA) is a drug used for the treatment of epilepsy, bipolar psychiatric disorders, and migraine. Previous studies have reported an increased generation of reactive oxygen species and oxidative stress in the toxic mechanism of VPA. Edaravone, a free radical scavenger for clinical use, can quench free radical reaction by trapping a variety of free radical species. In this study, effect of edaravone on some small intestine biochemical parameters in VPA-induced toxicity was investigated. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 51 publications
4
16
0
Order By: Relevance
“…Abnormal levels of ALP are closely related to a variety of pathological process and damage (Milan, 2006). Moreover, ALP activity has been associated with inflammatory process and tissue damage (Oktay et al, 2015). In our study, a significant increase was detected in the ALP activity of the Al group compared with the control group.…”
Section: Discussionsupporting
confidence: 55%
“…Abnormal levels of ALP are closely related to a variety of pathological process and damage (Milan, 2006). Moreover, ALP activity has been associated with inflammatory process and tissue damage (Oktay et al, 2015). In our study, a significant increase was detected in the ALP activity of the Al group compared with the control group.…”
Section: Discussionsupporting
confidence: 55%
“…Antiepileptic drugs increase ROS by several mechanism and cause some damages in certain tissues (2,30,31). In our previous study, significantly decreased GST activities and also, although the results were unsignificant, decreased SOD, CAT and GPx activities were found in the intestinal tissues of vPA group compared to controls (12). The results of this study were consisted with the previous studies related with the vPA toxicity (32)(33)(34)(35).…”
Section: Discussionsupporting
confidence: 78%
“…In experimental studies EDA has been suggested to show protective effects on inflammation and tissue damage by eliminating the deleterious effects of oxidants in various tissues (11)(12)(13). It acts as an antioxidant by quenching hydroxyl radicals and by preventing lipid peroxidation caused by hydroxyl radicals.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Oktay et al . () reported significantly decreased small intestine antioxidant enzyme activities and increased MDA levels in VPA group compared with the control group.…”
Section: Discussionmentioning
confidence: 91%
“…; Oktay et al . ). Excessive production of ROS can cause direct damage to cellular macromolecules, such as DNA, protein, and lipids, and can alter normal signaling pathways through activation of redox‐sensitive transcription factors.…”
Section: Introductionmentioning
confidence: 97%